Cluster analyses of contemporary embalming protocols in central European anatomy institutions: A collaborative effort to minimize chemical exposure - Mohebimoushaei, Sara; Antipova, Veronica; Biedermann, Uta; Brand-Saberi, Beate; Bräuer, Lars; Caspers, Svenja; Doll, Sara; Engelhardt, Maren; Filler, Timm J.; Gericke, Martin; Gümüsalan, Yakup; Gundlach, Stefanie; et al. (Annals of Anatomy-Anatomischer Anzeiger, 2025)
Background: Anatomical embalming forms a mainstay in the provision of teaching materials based on human post-mortem tissues. As a consequence of regulations worldwide to minimize the use of formaldehyde due to its harmful nature, effective measures must be taken to minimize its application in the anatomy laboratory. This study aimed to identify commonalities among embalming protocols used in Austrian, German and Swiss anatomies to reduce formaldehyde usage and provide a foundation for joint accreditation. Methods: Survey data on all procedures, technologies and chemicals related to embalming were collected from 28 participating institutions and analyzed using an automated clustering approach. Special attention was given to chemicals, explosion-proof facilities, and air ventilation technology. After conducting principal component analyses, the data was evaluated using an unsupervised K-means learning algorithm. Results: Six distinct clusters of common chemical usage were identified, namely (1) Thiel embalming with explosion-proof facilities, (2) potassium- and sodium salt-based embalming with downdraft ventilation, (3) ethanol/glycerin/glutaraldehyde/sodium alkyl ether sulphate-based embalming, (4) ethanol-based embalming, (5) formaldehyde-based embalming, and (6) ethanol/phenoxyethanol/alkyl (C12–16) dimethylbenzyl ammoniumchloride-based embalming. All clusters included the use of formaldehyde to varying extent. These clusters demonstrated high stability for fixation, combined fixation and conservation, as well as the incorporation of explosion-proof facilities and air ventilation technology. Moreover, a number of institutions used more than one similar protocol, so-called ‘Superclusters’, with Clusters (4) and (1) or Clusters (5) and (1) combined being the most common observation. Conclusion: These findings provide a basis for optimizing, streamlining and sharing embalming protocols among central European anatomy institutions.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cluster analysis; Conservation; Elbow method; Embalming; Fixation; Formaldehyde